Dental Trauma following Animal Attack: A Case Report - Meetkumar Dedania; Nimisha Shah; Sankalp Mahajan; Riddhi Thakkar (Journal of Clinical and Diagnostic Research)
Animal attacks are a common cause of human injuries worldwide, with human-leopard encounters frequently reported in India. Animal attack injuries are increasingly common in trauma centres due to human encroachment into wildlife habitats, leading to more human-animal interactions. These attacks, especially to the face, can cause significant functional, cosmetic, and structural damage. A 40-year-old woman was attacked by a leopard, resulting in tooth mobility, pain, and orofacial lacerations. Initial treatment and primary wound closure were performed in Ratlam, Madhya Pradesh, India. On further examination, necrosis with blackish discolouration of the left ala of the nose was observed, along with scarring on the lips. Tooth 22 exhibited luxation without alveolar bone involvement, leading to proclination. A multidisciplinary treatment approach was adopted, beginning with manual manipulation and repositioning of tooth 22, followed by stabilisation and endodontic treatment. For extraoral management, plastic surgery was performed, involving a paramedian forehead flap and alar cartilage remodelling using left auricular cartilage. The patient underwent follow-ups at one, three, six months and one year. In conclusion, managing dental trauma from animal attacks requires a multidisciplinary approach and ongoing follow-up. By fostering collaboration among healthcare professionals and ensuring vigilant care, we can significantly improve patient outcomes and recovery.